IMPLEMENTASI PERATURAN DAERAH KABUPATEN KARIMUN NOMOR 7 TAHUN 2013 MENGENAI PRASARANA DAN SARANA PENGELOLAAN SAMPAH TAHUN 2016-2017 - Sari, Devi Eka Kurnia; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Infrastructure and facilities of waste management is one of the important things that need to be considered in waste management. In accordance with Karimun Regency Regional Regulation number 7 of 2013 on infrastructure and facilities of waste management in chapter VI explain about infrastructure and facilities of waste management consisting of garbage trash, TPS/TPST, TPS 3R, TPA, and garbage transportation. The issue formulation of this research is why the implementation regional regulation of Karimun regency number 7 of 2013 about waste management infrastructure and facilities in 2016-2017 not effective yet?. This research purpose toknowing causes not effective yet the implementation regional regulation of Karimun regency number 7 of 2013 about waste management infrastructure and facilities in 2016-2017.In this research use one of four variables implementation theory George C. Edward III that is resource which consists of four aspects: (1) staff, (2) information, (3) authority and (4) facilities. This research use method approaches and types of qualitative research. This research was conducted at Office of Hausing, Residential Areas and Cleanliness Karimun regency. Data collection techniques with interview and documentation.Based on research results the concluded that: (1) lack of staff/ officers cleaning numbers and potential in each sub-regency of Karimun regency and there are several sub-regency don’t have staff cleaning, (2) regional regulation information on waste management, (3) no delegation of authority from Karimun regency government to sub-regency to carry out waste management, (4) many sub-regencies outside Karimun island don’t get infrastructure and facilities of waste management and lack of budget for provision the infrastructure and facilities of waste management.Keywords : Implementation, resource, infrastructure and facilities